1991
DOI: 10.3758/bf03197886
|View full text |Cite
|
Sign up to set email alerts
|

Loss of controllability in appetitive situations interferes with subsequent learning in aversive situations

Abstract: In two experiments, we examined whether or not a loss of control over food availability would interfere with subsequent two-way shuttle-escape learning. Rats that had experienced loss of control over food delivery were impaired in their acquisition of a shuttle-escape response, relative to the response-contingent and the continuous-reinforcement control rats (in Experiments 1 and 2) and to the lack-of-control and home cage control rats (in Experiment 2). Rats that had received noncontingent food delivery witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
10
1
1

Year Published

1992
1992
2005
2005

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 33 publications
3
10
1
1
Order By: Relevance
“…This phenomenon has been termed the learned helplessness effect; it has been hypothesized that learning about noncontingency between response and outcome produces the learning of uncontrollability, and results in deleterious effects (Maier & Seligman, 1976;Seligman, 1975). Some experiments found that the learning of uncontrollability in an appetitive situation interferes with subsequent learning in aversive or appetitive situation (Caspy & Lubow, 1981;Goodkin, 1976;Job, 1987Job, , 1988Job, , 1989Sonoda, Hirai, & Okayasu, 1992;Sonoda, Okayasu, & Hirai, 1991). These findings are formally similar to effects seen in experiments with pretreatment of uncontrollability over shock.…”
supporting
confidence: 78%
“…This phenomenon has been termed the learned helplessness effect; it has been hypothesized that learning about noncontingency between response and outcome produces the learning of uncontrollability, and results in deleterious effects (Maier & Seligman, 1976;Seligman, 1975). Some experiments found that the learning of uncontrollability in an appetitive situation interferes with subsequent learning in aversive or appetitive situation (Caspy & Lubow, 1981;Goodkin, 1976;Job, 1987Job, , 1988Job, , 1989Sonoda, Hirai, & Okayasu, 1992;Sonoda, Okayasu, & Hirai, 1991). These findings are formally similar to effects seen in experiments with pretreatment of uncontrollability over shock.…”
supporting
confidence: 78%
“…Eles confi rmam alguns estudos anteriores que não obtiveram desamparo em função da exposição prévia a estímulos apetitivos incontroláveis (Beaty & Maki, 1979;Calef & cols., 1984;Caspy & Lubow, 1981;Sonoda, Takahiro & Hirai, 1991) mas contradizem outros que relataram difi culdade de aprendizagem negativamente reforçada (Caspy, Formmer, Weiner & Lubow, 1979;Goodkin, 1976;Sonoda & Hirai, 1992). Esse confl ito de resultados aparentemente decorre de algumas diferenças de procedimento que difi cultam identifi car que variáveis podem ser as responsáveis Na sessão de teste, os sujeitos dos três grupos aprenderam a resposta de fuga.…”
Section: Discussionunclassified
“…The Skinner boxes employed in CRF training and pretreatment were the same as those used in Sonoda et al (1991). The Skinner boxes consisted of a chamber with clear Plexiglas sidewalls and ceiling, stainless steel front and rear walls, and a floor of stainless steel rods (1.6cm center to center).…”
Section: Apparatusmentioning
confidence: 99%
“…The lack-of-control rats showed only minor interference effects. Although Sonoda et al (1991) previously demonstrated this effect by using running responses as a test task, the present study examined its effect with a different response-diskpulling behavior. The present study also used a more sophisticated design in terms of: (a) making the acquisition of controllability on the CRF session equivalent among groups, by adding shaping before the CRF training phase, and (b) having FR 2 escape preceded by FR 1 escape during the test phase.…”
mentioning
confidence: 99%
See 1 more Smart Citation